The impact of everyday usage of different dental implant torque wrenches on their performance accuracy and repeatability: An in vitro study - Ilić Gavrilo; Milić-Lemić Aleksandra; Vulović Stefan; Marković Aleksa; Lazić Zoran; Dragović Miroslav; Todorović Aleksandar (Vojnosanitetski Pregled)
Background/Aim. The clinical success of prosthetic rehabilitation that commences after the attained implant osseointegration is dependent on the influence of several factors, of which screw loosening is a frequent one, and it is highly related to inadequate tightening (torquing) using torque wrenches. Although the wrenches are initially calibrated by the manufacturer, it is of great importance to evaluate their function after usage for a certain period of time. The aim of this study was to evaluate the accuracy and repeatability of the performance of implant torque wrenches in delivering necessary torque values before and after one year of usage. Methods. Two types of wrenches were used in the study: the beam-type and the toggle-type. Four various brands of beam-type wrench were marked as Beam 1 – Beam 4, and three various brands of toggle-type wrench were marked as Toggle 1 – Toggle 3, according to their design. Torque values delivered by wrenches were measured and analyzed using the One-Sample t-test, Independent-Samples t-test, and Mann-Whitney U test. The Bland-Altman bias test was used as an index of accuracy, whereas Forkman’s comparison of datasets coefficients of variation (CV) served as an index of repeatability. Results. All wrenches except new Beam 2 and Beam 3 showed differences between the average measured torque value and target torque value. Differences were found in the average measured values between all used and new wrenches. Higher bias was observed in Toggle 1, Toggle 2, and Toggle 3 brands, whereas lower bias was recorded between used and new Beam 1 and Beam 3 wrenches. When comparing the CV for used and new wrenches, Beam 1, Beam 4, Toggle 1, and Toggle 2 revealed differences, whereas the CV for Beam 2, Beam 3, and Toggle 3 did not differ significantly. Conclusion. Compared to toggle-type, the beam-type wrenches offer greater accuracy in achieving the target torque value. The torque deteriorates in all wrenches after aging/usage and is more prominent in toggle-type devices.